The physiological disorder of purple spot in loquat fruit: Etiology, possible causes and mitigation measures - Hadjipieri, Margarita; Georgiadou, Egli C.; Drogoudi, Pavlina D.; Fotopoulos, Vasileios; Badenes, Marisa Luisa; Manganaris, George A. (My University, 2021)
Loquat (Eriobotrya japonica Lindl) tree has a unique annual cycle that allows it to satisfactorily adapt in the Mediterranean basin but also in other subtropical climates. Over the recent years, the commercial production of loquat fruit has received increased interest and it has risen to a niche product that is greatly appreciated by the consumers. Accordingly, a considerable number of studies have been conducted in this crop over the last years. Depending on the cultivar and specific weather conditions, loquat fruit may suffer from purple spot. This physiological disorder affects the skin of the fruit prior to harvest, leading to skin discoloration with depressed purple surface. This physiological disorder has been poorly analyzed and it appears to be caused by a combination of the genotype considered, ripening stage, climatic conditions and the cultivation practices applied. Despite its economic impact, a limited number of information is available regarding the etiology and the practices for controlling it. This study provides an overview of the etiology, possible causes and mitigation measures to reduce the incidence and severity of such symptoms.
Keywords: Environmental conditions; Eriobotrya japonica; Gene transcription profiling; Preharvest disorder; Purple spot